European Union, Russia and the MH17 case: strategic narratives’ analysis (2014-2019) - Ramos, Paulo (2019)
The armed conflict that has erupted in Ukraine in 2014 has been affecting the way the states involved interact and how they seek to implement certain narratives in a new regional political context. While Russia has taken a more assertive stance in its neighbourhood through a narrative that seeks to contradict Western values promoted by the European Union (EU), the latter has shown some difficulty in presenting a coherent narrative in the face of developments over the past five years. In this sense, this article proposes to analyse the EU-Russia interaction, using as a case study the incident involving the crash of the Malaysia Airlines civil aircraft MH17. The analytical perspective combines elements of Role Theory - which here focuses on the interaction of states on the basis of certain expectations regarding their internal (national) and external (regional/international) roles - and Strategic Narratives. The differences between issue narratives (including regarding the Bellingcat Investigation Team narrative), system narratives and identity narratives are explored. The argument presented here is that the externalization of the EU issue narrative has emerged in two distinct ways - one more moderate in its official stance as an institution; another more assertive from the point of view of the work done by the East Stratcom Task Force (EATF). This ends up creating some dissonance in the way the European Union designs its narrative, and misalignment with the EU's narrative identity as a role state.